Governing collaborations: how boards engage with their communities in multi-academy trusts in England. Issue 4 (3rd April 2021) - Baxter, Jacqueline Aundree; Cornforth, Chris
ABSTRACT: Decentralization policy in English education has resulted Multi-Academy Trusts (MATs)-groups of schools governed and led by trustees. Research illustrates that many of these organizations are failing to connect with the school communities they serve. This paper uses documentary analysis and interviews with 30 MAT Board Members to examine this key area. The paper reveals that although there are some strategies in place to overcome this issue, that failure to implement fundamental processes such as communication strategies are leading to fragmentation and feelings of disconnect, and this raises questions as to the extent to which MATs are in touch with and serving their school communities.